Dialogue in Dialog: “Stem Cells?” (Dialog, 2001)
Ted Peters, The Stem Cell Controversy, p.290 Roger Willer, Moral Failure in the Stem Cell Controversy, p.294 Larry Rasmussen, Where the Moral Hazards Are in the Stem Cell Debate, p.296 Laurie Zoloth, The Duty to Heal an Unfinished World: Jewish Tradition and Genetic Research, p.299 Philip Hefner, There’s an Elephant in the Living Room, p.300